How Adverse Childhood Experiences and Gender Shape Perceptions of Synthetic Drug Use and Desistance in Yunnan, China - Monk-Turner, Elizabeth (Journal of drug issues, 2023)
Past research on illicit drug use and desistance has primarily been conducted in western countries, relied on quantitative data, and given little attention to potential gender differentiation. Utilizing qualitative data, we explore gender differences in how illicit drug users perceive the onset of use, whether or not they connect this to adverse childhood experiences (ACEs), and why they quit. The work is based on a sample of 24 informants from Yunnan. Women link onset of use to adverse childhood experiences (ACE) and report quitting primarily for their children. Men found support from their families helpful in ending illicit drug use. This adds qualitative support to theoretical work done by Wu and colleagues, Zhang, and Zhang and Demant who argue that familial attachment is critical in desistance. Utilizing a gendered lens, we gain and nuanced understanding of illicit drug use and links to ACEs which may better inform intervention programs.